THE INFLUENCE OF SOIL AND CLIMATIC FEATURES OF THE DRY-STEPPE ZONE OF CHESTNUT SOILS OF THE VOLGOGRAD REGION ON THE YIELD AND QUALITY OF NEW VARIETIES OF WINTER WHEAT - Vitaly L. Sapunkov; Andrey V. Guzenko (Siberian Journal of Life Sciences and Agriculture)
Background. In the conditions of the dry steppe zone of the Lower Volga region, winter soft wheat (Triticum aestivum L.) is considered the main food crop. It occupies about 2.0 million hectares of acreage in the Volgograd region. Basically, all farmers in our region sow time-tested varieties and do not pay attention to new varieties that are currently being bred by breeders.